The Effect of Self-esteem on Stress and Coping Mechanisms among Nursing Students during Clinical Training in Palestinian Universities - Dreidi, Mutaz; Abed, Duaa; Salameh, Haya; Abu Sbeih, Inass; Asmar, Saja; Salameh, Sewar; Asmar, Imad; Yaseen, Khalid; Al-Mahmoud, Omar; Almagharbeh, Wesam Taher (International Journal of Practice-based Learning in Health and Social Care, 2024)
Nursing students are exposed to a variety of stressors during their clinical training. The impact of stress must be considered as an important factor that may have negative impact on clinical performance and patient care. The purpose of this study was to identify the relationship between self-esteem and stress and coping mechanisms among nursing students during clinical practice. A descriptive-correlational study was used in the study; a self-reported questionnaire was used to collect the data. A convenience sample of 300 baccalaureate-nursing students from Palestinian universities and had clinical training in governmental and/or private hospitals participated in the study. The most common type of stressors perceived was stress from taking care of patients (Mean= 9.8), followed by stress from instructors and nursing staff (Mean= 8). Problem solving was the most prevalent coping strategy used by the participants (Mean= 14.2), followed by staying optimistic (Mean= 9). The results showed that avoidance, and transference have significant positive correlations with all stressors (p < 0.05), while self-esteem has significant negative correlation with all stressors. The findings of this study revealed that nursing students experienced mild to moderate stress, and the most prevalent form of stresses experienced was stress from taking care of patients, followed by stress from instructors and nursing staff. Students commonly used problem solving followed by staying optimistic to cope with their stress, and they found these methods to be effective.